Use of iron reactive anode in electrowinning of neodymium from neodymium oxide. (1st July 2019) - Abbasalizadeh, Aida; Seetharaman, Seshadri; Venkatesan, Prakash; Sietsma, Jilt; Yang, Yongxiang
Abstract: Electrolytic production of metallic neodymium is carried out in fused neodymium fluoride salts containing neodymium oxide. Two major challenges pertaining to neodymium production in fluoride salts are a) low solubility of neodymium oxide in fluoride melt, b) possibility of anodic gas evolution (CO, CO2, CF4, C2 F6 ). In this study, iron is used as a reactive anode in the electrolysis process, promoting electrochemical dissolution of iron into the melt, preventing PFC (perfluorocarbon) gas evolution at the anode. Further, the rare earth oxide is converted to rare earth fluoride by the use of iron fluoride formed as the result of iron dissolution. Thus, the fluoridizing agent is constantly regenerated in-situ which enables the continuous conversion of neodymium oxide feed. The cathodic product is NdFe alloy which can be used as a master alloy for the production of NdFeB magnets.